DESAIN MEDIA MENGGUNAKAN SOFTWARE PREZI DENGAN PENDEKATAN SCIENTIFIC MATERI HUKUM NEWTON TENTANG GERAK - Dinasari, Desti; Jufrida, Jufrida; Dani, Rahma (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2018)
This study aims to develop a medium of physics learning using software prezi with the scientific approach of Newton's law material on the movement of high school class X. This research includes research and development or Research and Development using 4D (Four-D) development procedures. The subjects of the trial in this study were students of Muaro Jambi 2 State Senior High School MIPA class X totaling 26 students. The research instruments used were material and media validation questionnaires and student perception questionnaires. Data analysis techniques of students' perceptions were carried out in descriptive statistics. Product specifications are prezi-shaped software using the exe format. The prezi advantage is easy to read because it uses the Zooming User Interface (ZUI) method which can enlarge and highlight certain parts that are being discussed. The results of the expert validation stated that the design used in accordance with the material title and learning objectives was declared valid. The test results of students' perceptions were 68.6 in very good categories and reliability in 0.835 in very high categories. Based on the results obtained that the media prezi with the scientific approach Newton's legal material about motion is suitable to be used as teaching material